2012
DOI: 10.54991/jop.2012.351
|View full text |Cite
|
Sign up to set email alerts
|

Palaeobotanical evidence of wildfire in the Upper Permian of India: Macroscopic charcoal remains from the Raniganj Formation, Damodar Basin

Abstract: Macroscopic fossil charcoal has been discovered in the carbonaceous shales associated with Seam-VI of Raniganj Formation, Upper Permian, Damodar Basin, India. A pycnoxylic gymnosperm wood is described and confirms the occurrence of palaeo-wildfire in this area during the Late Permian. The integration of the data presented in the current study with previously published data for the Raniganj Formation, principally related to the occurrence of (pyrogenic) inertinites within coal layers, demonstrates that palaeo-w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
(37 reference statements)
0
2
0
Order By: Relevance
“…Later on, macro-charcoal has been discovered by different workers in the Permian sequences of South Africa (e.g., Glasspool, 2003;Jasper et al, 2013), Brazil (e.g., Jasper et al, 2008, 2011a, b, c, 2013Degani-Schmidt et al, 2015;Manfroi et al, 2015;Kauffmann et al, 2016;Benício et al, 2019;Kubik et al, 2020), Australia (e.g., Mays & McLoughlin, 2022), the Arabian Plate (e.g., Uhl et al, 2007); and Antarctica (e.g., Holdgate et al, 2005;Slater et al, 2015;Tewari et al, 2015). The first verified (by means of SEM analysis) records of macro-charcoal from the Indian subcontinent, were published by Jasper et al (2012), who reported the existence of wildfire at the time of deposition of the late Permian Raniganj Formation in the Raniganj Coalfield of the Damodar Basin. Later on, Mahesh et al (2015Mahesh et al ( , 2017 identified macrocharcoal from the late Permian Barren Measures and Raniganj formations of the South Karanpura Coalfield, Damodar Basin and the late Permian (Lopningian) of the Mand-Raigarh Coalfield, Mahanadi Basin.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…Later on, macro-charcoal has been discovered by different workers in the Permian sequences of South Africa (e.g., Glasspool, 2003;Jasper et al, 2013), Brazil (e.g., Jasper et al, 2008, 2011a, b, c, 2013Degani-Schmidt et al, 2015;Manfroi et al, 2015;Kauffmann et al, 2016;Benício et al, 2019;Kubik et al, 2020), Australia (e.g., Mays & McLoughlin, 2022), the Arabian Plate (e.g., Uhl et al, 2007); and Antarctica (e.g., Holdgate et al, 2005;Slater et al, 2015;Tewari et al, 2015). The first verified (by means of SEM analysis) records of macro-charcoal from the Indian subcontinent, were published by Jasper et al (2012), who reported the existence of wildfire at the time of deposition of the late Permian Raniganj Formation in the Raniganj Coalfield of the Damodar Basin. Later on, Mahesh et al (2015Mahesh et al ( , 2017 identified macrocharcoal from the late Permian Barren Measures and Raniganj formations of the South Karanpura Coalfield, Damodar Basin and the late Permian (Lopningian) of the Mand-Raigarh Coalfield, Mahanadi Basin.…”
Section: Introductionmentioning
confidence: 81%
“…Charcoal of gymnospermous affinity dominates so far all charcoal assemblages described from the Permian of India (e.g. Jasper et al, 2012Jasper et al, , 2016Jasper et al, , 2017Mahesh et al, 2015Mahesh et al, , 2017Murthy et al, 2020aMurthy et al, , 2021Murthy et al, , 2022Mishra et al, 2021Mishra et al, , 2022, but also other parts of Gondwana (S-America: Jasper et al, 2008Jasper et al, , 2011aJasper et al, , b, c, 2013Degani-Schmidt et al, 2015;Manfroi et al, 2015;Kauffmann et al, 2016;Benício et al, 2019;Kubik et al, 2020;Jordan: Uhl et al, 2007;Antarctica: Holdgate et al, 2005;Slater et al, 2015;Africa: Glasspool, 2003;Jasper et al, 2013;Australia: Mays & McLoughlin 2022), as well as Euramerica (e.g. Uhl & Kerp, 2003;Uhl et al, 2004).…”
Section: Densipollenites Indicus and Potonieisporites Novicusmentioning
confidence: 99%
“…Jasper et al, 2008, 2011a, Degani-Schmidt et al, 2015Manfroi et al 2015b;Kauffmann et al, 2016;Benício et al, 2019a;Kubik et al, 2020), India (e.g. Jasper et al, 2012Jasper et al, , 2013Jasper et al, , 2016aJasper et al, , b, 2017Murthy et al, 2021); South Africa (e.g. Glasspool, 2000Glasspool, , 2003a and Antarctica (e.g.…”
Section: Permianmentioning
confidence: 99%
“…However, wildfires were frequent and widespread throughout the late Permian (Lopingian Epoch; 259.51-251.9 Ma), the interval leading up to the EPE, without any accompanying major biodiversity loss or discernible ecosystem disruption. Evidence for global fire-prone conditions during the Lopingian has grown steadily in the last 20 years, such as abundant macroscopic charcoal (or macro-charcoal) in Antarctica (Tewari et al 2015), Australia (Glasspool 2000;McLoughlin et al 2019), Europe (Uhl and Kerp 2003;Uhl et al 2012;Kustatscher et al 2017), Brazil (Kauffmann et al 2016), China (Yan et al 2019;Xiao et al 2020), Jordan (Uhl et al 2007), and south Asia (Jasper et al 2012(Jasper et al , 2016a(Jasper et al , 2016bMahesh et al 2015;Shivanna et al 2017). Similarly, abundance trends of 'inertinite' (see Materials and Methods) have indicated significant fluctuations in wildfire activity during the Lopingian, but upon a background of relatively high fire activity (Diessel 2010;Glasspool and Scott 2010;Glasspool et al 2015).…”
Section: Introductionmentioning
confidence: 99%